Odpowiedzi

Najlepsza Odpowiedź!
2009-12-20T19:47:42+01:00
D. x^+4x+3x+3=x^*7x+x+7
3+7=x^-x^+6x-4x-3x
10=2x-3x
10=-x
x=-10
b. x^+4x+3x+12=0
x^+7x=-12
c. -x^=-2x+12
-x^+2x=12
e. x^+4+4x=4x^+9-4
x^+4+4x=4x^+5
x^-4x^+4x=1
-3x^+4x=1
g. x^-3/5+10/5=x^-3
7/5=-3
h.1+2= -3x^+2x
3=-3x^+2x
i. -(2x-3)(x-4)=3(4+x)
-2x^+8x+3x-12=12+3x
-2x^+11x-3x=24
-2x^+8x=24
2009-12-20T19:53:59+01:00
(x+1)^=4x-2
x²+2x+1=4x-2
x²-2x+3=0
liczymy delte
Δ=b²-4ac
Δ=(-2)²-4*1*3
Δ=4-12
Δ=-12 nie ma rozwiązania

(x+3)(x+4)=0
x²+4x+3x+12=0
x²+7x+12=0 a=1 b=7 c=12
Δ=b²-4ac
Δ=7²-4*1*12
Δ=49-48
Δ=1
x₁=-b-√Δ/2a=-7-1/2*1=-8/2=-4
x₂=-b+√Δ/2a=-7+1/2*1=-6/2=-3

-x^=-2(x-6)
-x²=-2x+12
-x²+2x-12=0
Δ=b²-4ac
Δ=2²-4*(-1)*(-12)
Δ=4-48
Δ=-44 nie ma rozwiązania

(x+3)(x+1)=(x-1)(x+7)
x²+x+3x+3=x²+7x-x-7
x²-x²+x+3x-7x+x=-7-3
-2x=-10/:(-2)
x=5

(x+2)^+4x=(2x+3)^-4
x²+4x+4+4x=4x²+6x+9-4
x²-4x²+4x+4x-6x+4-9+4=0
-3x²+2x-1=0
Δ=b²-4ac
Δ=2²-4*(-3)*(-1)
Δ=4-12=-8 nie ma rozwiązania

x^-x=-(x-3)-11
x²-x=-x+3-11
x²-x+x-3+11=0
x²+9=0
nie ma rozwiązania delta jest ujemna

x^+2x+1=-2x^+4x-2
x²+2x²+2x-4x+1+2=0
3x²-2x+3=0
Δ=b²-4ac
Δ=(-2)²-4*3*3
Δ=4-36=-32

-(2x-3)(x-4)=3(4+x)
-(2x²-8x-3x+12)=12+3x
-2x²+8x+3x-12=12+3x
-2x²+8x=0
Δ=b²-4ac
Δ=8²-4*(-2)*0
Δ=64
x₁=-b-√Δ/2a=-8-8/2*(-2)=-16/-4=4
x₂=-b+√Δ/2a=-8+8/2*(-2)=0/-4=0

g. x *x-3/5 +2=(x-1)^-2 nie wiem jak zrobic pozdrawiam